Effects of Planning Aids and Presentation Media on Performance and Affective Responses in Strategic Decision-Making - Schwenk, Charles R. (Management Science, 1984)
The Dialectical Inquiry System (DIS) and the Devil's Advocate (DA) have been recommended as strategic decision-making aids and as improvements on the traditional expert (E) approach in which strategic decisions are based on preliminary analyses and proposals by staff experts. Previous research on the effects of the DIS and DA has produced conflicting results. In the present study, subjects produced alternative strategies and recommendations for a company described in a case. They were given the E, DA, or DIS treatment either in written form or via videotape. In addition, some were assigned to a control (C) group and received no planning assistance. The results showed that the written DA, the videotape DI, and the videotape E treatment caused subjects to generate fewer functional area alternatives than the C subjects. Further, the subjects receiving the written DA generated more strategic alternatives than those receiving the written DIS or E. The DA also reduced the effects of an “expert report” on subjects' final recommendations while the DIS did not. Subjects given the DA and DIS reported greater satisfaction with the process than those given the E.